CD44 as a novel therapeutic target in pulmonary arterial hypertension: Insights from multi-omics integration and molecular docking - Wei Chen; Lingling Zhang; Haiyan Qi (PLoS ONE, 2025)
Pulmonary arterial hypertension (PAH) is a progressive and often fatal disorder characterized by increased pulmonary vascular resistance and subsequent right heart failure. Inflammation plays a pivotal role in the pathogenesis of PAH, and recent studies have highlighted the potential therapeutic significance of targeting inflammatory pathways. This study investigates the role of CD44, a cell surface receptor, in the inflammatory processes underlying PAH. By analyzing bulk RNA-seq data from idiopathic pulmonary hypertension (IPAH) patients and conducting single-cell RNA-seq analysis on pulmonary arterial cells, we identified CD44 as a key modulator of inflammation. Our findings suggest that elevated CD44 expression is not only in T cells but also prominently in pulmonary artery smooth muscle cells (SMCs), suggesting its involvement in vascular inflammation and remodeling. Molecular docking studies revealed a potential interaction between CD44 and progesterone, an anti-inflammatory drug and immunomodulator, and this indicates a novel avenue for therapeutic intervention. The results support the hypothesis that targeting CD44 may reduce inflammation and improve clinical outcomes in PAH patients.